Evaluation of diagnostic advances in musculoskeletal tuberculosis; the automated xpert MTB/RIF assay - Held, Michael (Department of Health and Rehabilitation Sciences, 2016)
The aim of this thesis was to investigate the diagnostic accuracy of Xpert for musculoskeletal TB and for rifampicin resistance against a gold standard of culture or histology. Site of disease, HIV status, and age of patients, and accuracy in spinal compared to extraspinal TB were investigated as secondary objectives. The overarching hypothesis was that Xpert is more accurate and would provide results faster than the gold standard for musculoskeletal TB, and that it would have a higher yield in HIV infected patients, adult patients, and patients with spinal disease.